Can Presurgical Ultrasound Predict Survival in Women With Ovarian Masses?. Issue 1 (March 2019) - Mubarak, Ahmad Iyad; Morani, Ajaykumar C.; Samuel, Jessica; Sun, Jia; Wei, Wei; Bhosale, Priya R.
Abstract : Purpose: This study aimed to determine the ability of ultrasound to predict survival and detect more aggressive tumors in women with ovarian masses. Materials and methods: Institutional review board approval was obtained. A total of 167 patients who presented with adnexal mass/masses were included. These were documented as benign or malignant on ultrasound. Age, date of diagnosis and date of death, type of tumor, and tumor marker cancer antigen 125 (CA-125) values were recorded. A CA-125 value of less than 35 U/mL was considered normal. All cases underwent surgery. Pathologic findings were considered as reference standard. The 2 × 2 cross-tabulations were used to correlate dichotomized CA-125, US diagnosis (benign vs malignant), and pathologic status. Difference of distributions was tested using the Wilcoxon rank sum test, and their association was tested using the Fisher exact test. All tests were 2-sided, and P values of 0.05 or less were considered statistically significant. Kaplan-Meir curves were generated to estimate survival. Results: There was a statistically significant difference in patients with benign versus malignant tumors based on pathology ( P < 0.0001) and ultrasound ( P < 0.0003). Sensitivity, specificity, positive predictive value, negative predictive value, and accuracy of ultrasound were 55%, 86%, 90% and 46%, and 81%. Patients diagnosed as having malignant tumors based on ultrasound had statistically significant worse overall survival. Probability of survival based on pathologic diagnosis of malignancy was statistically significant at P < 0.0003; based on ultrasound, P < 0.0001; and based on CA-125, P < 0.041. Conclusion: Patients who had ultrasound-based prediction of ovarian malignancy had overall worse survival probability ( P < 0.0001) compared with CA-125– or pathology-based prediction.